Patient satisfaction at the chronic pain management clinic at Groote Schuur hospital - Majangara, Munyaradzi Blessing (Department of Anaesthesia and Perioperative Medicine, 2023)
Background: Chronic pain is a costly and debilitating ailment with an estimated global prevalence of 20%. The evaluation of patient satisfaction with pain management is crucial to ensure that care provided remains fit for purpose, and it helps to identify opportunities for improvement. Groote Schuur Hospital has one of the few functional interdisciplinary pain clinics in South Africa with more than 900 patients seen per year. To date we have no data informing us about patient satisfaction at the clinic. The aim of our study was to survey patients being treated at the pain clinic to determine their level of satisfaction with the service. Methods: A descriptive cross-sectional study was conducted with a sample of 67 patients who had been attending the Chronic Pain Management Clinic for more than 3 months. Data were collected telephonically using the patient demographics form and internationally validated Pain Treatment Satisfaction Scale. Data were analysed using descriptive statistics. Results: The mean age of the 67 participants was 56.5yrs (SD: 12.9; Age range: 18-83). Eighty-one percent of the sample identified as female, and 70% had not completed 12 years of schooling. Most patients were referred from orthopaedics (48%) followed by referrals from day clinics (13.5%). The median pain severity score was 7.5 (IQR: 7-9) a week prior to data collection. The majority (70%) of participants reported that they were able to ask the staff questions and were provided with adequate support and care. Results indicate that 6 in every 10 patients are satisfied with their pain management at the GSH chronic pain management clinic. One aspect of care which was less than satisfactory related to receiving information about their condition and treatment. In general, participants would have liked more information about their illness or injury (51%), causes and treatments for pain, as well as side effects of pain medication (60%). Conclusions: Most participants were somewhat satisfied or very satisfied with all aspects of care they were asked about. It is clear that patient-satisfaction is not only driven by pain relief but can be enhanced by good patient-provider relationships and shared decision making. It is important to continually train health care providers to improve their communication skills.